How Do Extra Role Behaviors Affect Sales People Performance An Emprical Examination - Koç, Umut; Torlak, Ömer; PAKSOY, MAHMUT (My University, 2007)
Customer orientation and organizational citizenship behaviors (OCBs) are two forms of extra-role behaviors that are expected to affect organizational performance positively in the literature. This study aims to examine the relationship between customer orientation of salespeople who work for the pharmaceutical industry and superstore retailing sectors. In addition, their OCBs and the effect of these constructs on salespeople performance are explored. The research uses the scales developed by Stock and Hoyer (2002), MacKenzie, Podsakoff, and Fetter (1993) and Roman and Munuera (2005) to measure customer orientation, OCBs, and performance respectively. The results show a significant relationship between customer orientation and OCBs. OCBs affect salespeople’s performance positively and this behavior differs according to sectors.
Keywords: Customer Orientation; Extra-role Behaviors; Organizational Citizenship Behaviors; Salespeople Performance